PENGARUH PROFITABILITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE - Indira Shinta Dewi shinta (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
Obtaining empirical evidence of how the effect of profitability, leverage, and income growth on tax avoidance is the goal of this study This study focused on manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2016-2020. 317 number of observations sample obtained by the method nonprobability sampling purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The analysis showed that the profitability, and leverage has no effect on tax avoidance. Sales growth has negative effect on tax avoidance. Keywords : leverage; sales growth, profitability; tax avoidance